Potential of Goletrak Grass (Borreria alata) as Suplementation on Hay Multinutrient Waffle and Its Nutrition Value to Improve Growth Performance in Rabbit (Oryctolagus cuniculus) - Widayati, Okti; Syaefullah, Bangkit Lutfiaji; Isty, Gallusia Marhaeny Nur; Cahyo, Hendra Nur (Buletin Peternakan, 2025)
The aim of this study was to determine the effects of goletrak grass (Borreria alata) as suplementation in hay multinutrient waffle on the growth performance in rabbit (Oryctolagus cuniculus). The experiment was carried out in 2 stages consisting of hay multinutrient waffle (HMW) production and feeding application in rabbit. The HMW was produced in three formulations: H1 was used 5% Boreria alata; H2 10% Boreria alata; and H315% Boreria alata. Physical and chemical assessment of HMW were performed to evaluate the feed quality prior to feeding application. A total of 18 local rabbit males (Oryctolagus cuniculus) were assigned to 6 dietary treatments, 3 animals each, consisted: T01 = 100% benggala grass; T02 = 60% commercial pellet + 40% benggala grass; T1 = 60% commercial pellet + 40 % HMW; T2 = 40% commercial pellet + 60 % HMW; T3 = 20% commercial pellet + 80 % HMW; and T4 = 100 % HMW. The addition of goletrak grass (Boreria alata) had no significant effect (p>0.05) on physical propertiesincluding colours, texture, aroma, hardness, and durability index. However, significant effects (p<0.05) were observed on the chemical quality such as fat and nitrogen free extract. The effect of HMW feeding had significant effects (p<0.05) on feed conversion ratio (FCR), body weight gain and average daily gain (ADG), but it had no significant effect (p>0.05) on feed consumption. In conclusion, 15% inclusion of Boreria alata into HMW formulation, with 40% HMW in the diet, resulted in improved FCR, along with increased total weight gain and ADG. These findings suggest a beneficial impact of Boreria alata inclusion of performance and feed efficiency in rabbit.